Sistem Pengiriman Barang Berbasis Web pada PT Prabu Expressindo - Elidjen, Elidjen; Tanun, Shellyana; Saputro, Anggoro Dwi; Simolang, Nicky Laurens (Bina Nusantara University, 2011)
PT Prabu Expressindo which has carried on business in freight services since 1999 finds several constraints associated with ease of services access for the service users. Those constraints become the background of the web-based delivery system development with the primary objective to overcome the difficulties of service access and goods delivery and to add some features to facilitate the service users in communicating with the PT Prabu Expressindo. The linear sequential process model is used to develop the overall system and the literary study is used to enrich the insight to develop a better system. The user friendly system obtains a lot of information which in turn facilitates the goods delivery.